Efficient Surface Passivation and Electron Transport Enable Low Temperature-Processed Inverted Perovskite Solar Cells with Efficiency over 20% - Wang, Helin; Yang, Fu; Li, Ning; Kamarudin, Muhammad Akmal; Qu, Junle; Song, Jun; Hayase, Shuzi; Brabec, Christoph (ACS Sustainable Chemistry & Engineering, 2020)
PCBM is a fullerene derivative, which is commonly employed as an electron transport layer (ETL), and still has some issues to fabricate low temperature-processed perovskite solar cells (PSCs) such as surface trap states, low electron mobility, and extra recombination losses at the perovskite/PCBM interface. Herein, a novel perylene diimide dimer (2FBT2FPDI) is synthesized and employed as an ETL or intermediary layer to overcome these challenges. Owing to its suitable energy levels and high electron mobility, 2FBT2FPDI shows great potential to serve as a promising efficient ETL in the photovoltaic devices. Moreover, 2FBT2FPDI can coordinate with the lead site of the perovskite surface, which helps to heal the surface defects and suppress charge-trapped recombination. Therefore, the performance of PSCs is greatly improved from 17.3 to 20.3%, when 2FBT2FPDI was used as the intermediary layer to assist the growth of the PCBM film. This work presents a new direction through interface engineering with n-type nonfullerene small molecules for low temperature-processed stable and highly efficient inverted PSCs.<br
Keywords: perovskite solar cell; surface passivation; electron transport material; high efficiency; device stability